ANALISIS KANDUNGAN PROTEIN PADA LOBSTER PASIR (PANULIRUS HOMARUS) YANG DIBUDIDAYAKAN DI DUSUN TELONG-ELONG KABUPATEN LOMBOK TIMUR - Afni Isriani; Mita Ayu Liliyanti; Lalu Achmad Tan Tilar Wangsajati Sukmaring Kalih (Universitas Mataram, 2022)
The high demand for lobster creates opportunities and challenges for farmers. Telong-elong Hamlet is one of the sites for the development of lobster cultivation activities. The feed used by cultivators is diverse and is obtained easily because the supply is abundant at an affordable price when compared to commercial pelleted feed. This has an impact on the quality of the lobster produced. This community service activity and research aims to determine the protein content of the cultured sand lobster (P. homarus) and the effect of feeding on growth. The approach method used is descriptive with interview data collection methods, observation and testing. Sand lobsters were given different feeds, namely fresh trash, salted trash and snails, data collection was carried out 3 times every 2 weeks. The results showed that sand lobster fed fresh trash had the highest protein content (27.10%), salted trash feed (25.78%) and snail feed (24.66%). There is a positive and strong linear regression relationship between feed protein and protein in sand lobster meat (r2 = 0.95). Sand lobster fed fresh trash produced the highest weight SGR (2.54 g/day) and the highest length SGR (0.82 mm/day). The relationship between lobster weight and length was linear positive but not very strong (r2 = 0.587) and positive allometric (weight growth was faster than length growth). Fresh trash feed produced the highest protein in meat and growth. It is recommended to use fresh trash fish which has a significant effect on the final quality of aquaculture products and their growth, so that the results of this activity are applicable and beneficial for the lobster cultivating community in reducing maintenance costs and contributing to the development of sustainable lobster cultivation activities.